Stoichiometrically driven disorder and local diffusion in NMC cathodes. Issue 16 (19th April 2021) - Ashton, Thomas E.; Baker, Peter J.; Sotelo-Vazquez, Carlos; Footer, Charles J. M.; Kojima, Kenji. M.; Matsukawa, Takeshi; Kamiyama, Takashi; Darr, Jawwad A.
Abstract : Neutron powder diffraction has uncovered major stoichiometry-driven structural differences in NMC cathodes otherwise obscured in lab-based X-ray powder diffraction. The atomic scale Li diffusion has also been probed by muon spin relaxation. Abstract : Major structural differences in lithium nickel manganese cobalt oxides (NMC) prepared under identical conditions have been uncovered using neutron powder diffraction. Sample NMC-622 was obtained as a single R 3̄ m crystal structure with little defects, whereas NMC-811 showed significant Li deficiency and NMC-433 formed three distinct phases; ordered R 3̄ m, disordered R 3̄ m and a C 2/ m phase. Local diffusion behaviour was also studied by muon spin relaxation (μSR). It was observed that single phase R 3̄ m NMC-622 showed a higher lithium diffusion coefficient (4.4 × 10 −11 cm 2 s −1 ) compared to lithium deficient NMC-811 (2.9 × 10 −11 cm 2 s −1 ), or the highly disordered NMC-433 (3.4 × 10 −11 cm 2 s −1 ). Furthermore, activation energies for the Li diffusion process were estimated to be 58 meV, 61 meV and 28 meV for NMC-811, NMC-622 and NMC-433, respectively.